2020
DOI: 10.14218/jcth.2020.00032
|View full text |Cite
|
Sign up to set email alerts
|

Changing Population of Liver Transplant Recipients in the Era of Direct-acting Antiviral Therapy

Abstract: Background and Aims: With the availability of direct-acting antiviral (DAA) therapy for hepatitis C virus (HCV) infection and changing liver disease etiology for liver transplantation (LT), data on the changes in LT recipient population in the DAA era are scanty. Methods: The United Network for Organ Sharing (UNOS) registry (01/2007 to 06/2018) was used to develop a retrospective cohort of LT recipients for HCV, alcohol-associated liver disease (ALD), and non-alcoholic steatohepatitis (NASH). LT recipients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This finding is in alignment to previous reports with NASH etiology as the fastest growing indication for use of SLK, likely due to concomitant comorbidities such as diabetes, hypertension, and obesity 20 . Among candidates listed for LT alone who have renal dysfunction at listing, ALD etiology was most strongly associated with receipt of LT, likely due to presence of concomitant alcoholic hepatitis with severe disease and younger age in this population 29,30 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is in alignment to previous reports with NASH etiology as the fastest growing indication for use of SLK, likely due to concomitant comorbidities such as diabetes, hypertension, and obesity 20 . Among candidates listed for LT alone who have renal dysfunction at listing, ALD etiology was most strongly associated with receipt of LT, likely due to presence of concomitant alcoholic hepatitis with severe disease and younger age in this population 29,30 …”
Section: Discussionsupporting
confidence: 86%
“…20 Among candidates listed for LT alone who have renal dysfunction at listing, ALD etiology was most strongly associated with receipt of LT, likely due to presence of concomitant alcoholic hepatitis with severe disease and younger age in this population. 29,30 Analysis using the UNOS database with a large sample size is a strength of our study. Using extended data until June 2020, our study confirmed recently reported findings on SLK and use of kidney after LT alone.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is most likely due to the wide availability of curative therapy for chronic HCV infection, which reduces the rates of HCC. 2 , 16 19 Notably, the proportion of those with HBV-HCC requiring a transplant remained low and decreased further over time, suggesting the positive impact of antiviral therapy and preventive HBV vaccination. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%